Kuhn and the question of pursuit worthiness - Šešelja, Dunja; Straßer, Christian (Topoi - An International review of philosophy, 2013)
The aim of this paper is, on the one hand, to critically investigate Kuhn's stance on the assessment of the pursuit worthiness of scientific theories, and, on the other hand, to show the actuality of some of Kuhn's points on this issue, in view of their critical analysis. To this end we show that Kuhn presents certain tools, which may help scientists to overcome communication breakdowns when engaging in the process of rational deliberation regarding the question whether a theory is worthy of further pursuit. These tools are persuasion, translation and interpretation. However, we argue that the perspective of epistemic semantic monism present in Kuhn's work obstructs the full applicability of these tools. We show that dropping this perspective makes the notions of persuasion and interpretation more fruitful, and moreover, allows for a pluralism of scientific theories and practices that complements the pluralism based on disagreement among scientists, emphasized by Kuhn.